The Primary Care Toolkit Practical Resources for the Integrated Behavioral Care Provider - O'Donohue, William T.; James, Larry. (Springer New York, 2009)
The Primary Care Toolkit Practical Resources for the Integrated Behavioral Care Provider Edited by Larry James, Tripler Army Medical Center, Honolulu and William ODonohue, University of Nevada, Reno Im working in a primary care facility. Now&what am I doing here? Ideally, the integration of behavioral health into the medical setting brings effective, coordinated treatment and increased satisfaction for both practitioner and patient. In reality, however, the results can be far from perfectand far from integrated. The Primary Care Toolkit introduces mental health professionals to the best possibilities for the collaboration while preparing them for the crucial differences between primary care and traditional mental health settings, to make the transition as worthwhile and non-traumatic as possible. The editors, experts on collaborative care (and astute judges of its potentials and pitfalls), have packed the Toolkit with hands-on, evidence-based, practical information, including handouts, protocols, inventories, and reference lists. Readers will improve their medical literacy, learn how to make more effective use of the clinics patient education and marketing resources, and uncover key consultation skills. And chapters for primary care physicians and administrators help all parties understand the synergy underlying integrative care. A sampling of the Toolkits features: Assessment and treatment guidelines for core illnesses (chronic pain, heart disease, anxiety, depression), and issues (treatment compliance, obesity, smoking, somatization) encountered in primary care. Hiring and interview protocols for administrators. Training programs and issues. Financial and billing models. Quality management/improvement tools. Review of the current CPT codes. The Primary Care Toolkit is a safety net for the clinician adjusting to collaborative practice, giving new "team players"clinical and health psychologists, psychiatrists, mental health nurses, and clinical social workers, as well as the professionals working with themgreater confidence and competence.